Changes in soil macropores: Superposition of the roles of organic nutrient amendments and the greenhouse pattern in vegetable plantations. (12th April 2019) - Xu, Lingying; Wang, Meiyan; Tian, Yutian; Shi, Xuezheng; Shi, Yijie; Yu, Quanbo; Xu, Shengxiang; Li, Xiangwei; Xie, Xinqiao
Abstract: Organic farming can potentially mitigate soil compaction, which commonly occurs in vegetable plantations, particularly in greenhouses when compared with open‐air systems. Although several studies have addressed the effect of planting patterns on soil pore characteristics, few studies have focused on changes in pore attributes under organic fertilization. We used adjacent fields during green manure planting as a control to compare the differences in soil physicochemical and macropore parameters between 14‐year‐old greenhouse plots and open‐air plots under organic fertilization. Pearson's correlation analysis was performed to analyse the drivers of soil macropore characteristics in vegetable plantations in Jiangsu Province, China. A significant increase in connectivity, fractal dimensions and total macroporosity and a decrease in bulk density after 14 years of organic farming, particularly in the surface layer in the greenhouse, were observed. However, the difference in pores in the plough pan layer was not significant between the treatments. The volume of small pores (50–500 μm) and medium pores (500–1, 000 μm) increased significantly ( p < 0.05) in both the greenhouse and open‐air systems, showing significantly positive relationships with soil organic matter (SOM) and total nitrogen (TN) content. Large pores (>1, 000 μm) showed a clear decrease, especially in open‐air fields, possibly due to the disappearance of the original straw residues in the surface layer. Small and medium pores in the plough layer increased in greenhouse fields, whereas the opposite occurred in open‐air fields. Overall, compared with open‐air systems, long‐term organic greenhouse patterns had a significantly positive effect on soil pore attributes.